2015
DOI: 10.2139/ssrn.2679218
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Factor Cointegrated Commodity Price Model with an Application to Spread Option Pricing

Abstract: In this paper, we propose an easy-to-use yet comprehensive model for a system of cointegrated commodity prices. While retaining the exponential affine structure of previous approaches, our model allows for an arbitrary number of cointegration relationships. We show that the cointegration component allows capturing well-known features of commodity prices, i.e., upward sloping (contango) and downward sloping (backwardation) term-structures, smaller volatilities for longer maturities and an upward sloping correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 48 publications
(21 reference statements)
0
14
0
Order By: Relevance
“…We employed the continuous time model of cointegrated commodity prices developed in Farkas et al [6] and conducted a simulation study for a cointegrated system of three commodities. We calculated the prices of several spread options and found that cointegration significantly influences these prices.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We employed the continuous time model of cointegrated commodity prices developed in Farkas et al [6] and conducted a simulation study for a cointegrated system of three commodities. We calculated the prices of several spread options and found that cointegration significantly influences these prices.…”
Section: Discussionmentioning
confidence: 99%
“…Before proceeding to the simulation study, in this section we present for the sake of completeness, a short description of the model developed in Farkas et al [6].…”
Section: Outline Of the Modelmentioning
confidence: 99%
See 3 more Smart Citations